ShopeePay: How Security Perception and Ease of Use among Its Users Would Affect Loyalty through Trust in Pontianak - Diwani Fara Sagita; Muhammad Ebuziyya Alif Ramadhan; Helman Fachri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of Security Perception and Ease of Use on Loyalty through Trust in choosing to conduct transactions using ShopeePay in Pontianak City. This research employs an associative method. The population in this study consists of all ShopeePay users domiciled in Pontianak City, with a sample size of 100 respondents determined using purposive sampling technique. The data analysis technique in this study uses Structural Equation Modeling (SEM) with the assistance of SmartPLS Version 3 software. The data testing in this study consists of testing the outer model and the inner model. Inner model testing includes tests for convergent and discriminant validity, Average Variance Extracted (AVE), and Reliability Testing. Meanwhile, outer model testing consists of R-Square testing, direct effect, and indirect effect testing. This research is motivated by the empirical gap concerning the role of trust as an intervening variable in the relationship between security perception and ease of use on user loyalty in digital payment services, where most previous studies have emphasized the direct influence of these two variables on loyalty. In Pontianak City, studies on ShopeePay that integrate trust as a mediating variable remain very limited. The novelty of this research lies in the finding of a full mediation model, in which security perception and ease of use significantly influence trust, trust significantly influences loyalty, yet neither security perception nor ease of use exerts a direct influence on loyalty. Theoretically, this research confirms the position of trust as a key determinant in building e-wallet user loyalty and enriches the development of the Technology Acceptance Model and loyalty within the context of financial technology at the regional level. Based on the direct effect analysis results, it is found that security perception and ease of use have a direct influence on trust, and trust subsequently has a direct influence on user loyalty. However, security perception and ease of use do not have a direct influence on loyalty. Furthermore, based on the indirect effect test results, it is known that both security perception and ease of use influence user loyalty through the mediating role of trust.